COVID19: RISK MANAGEMENT WITH SPECIAL REFERENCE TO ORGANIZATIONS AND THEIR RESISTANCE - Keković, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The scientific and professional public often debates whether and to what extent risk management, as a management concept based on risk assessment, is part of the solution or rather part of the problem in situations of high uncertainty, which is called non-routine environment. If it is part of the solution, then crisis management and crisis plans can be considered as an extension of the concept of risk management in crisis conditions. Risk management is part of the problem if the decision-making process is based on misjudgments, which can harm the organization in the long run and threaten its fundamental values. Organizations have responded to the COVID19 pandemic with a very wide range of management functions and capabilities: risk management, emergency, business continuity, or crisis. In practice, these concepts and management functions have been interconnected, and responses have been generaly recognized by situational behavior and pragmatic approaches. However, what we can agree is that the lack of key risk information, as an input for risk assessments, has questioned the implementation of the traditional concept of risk management based on historical data, statistics, and cost-benefit analysis. As a result, the answers were confusing and contradictory. It has been confirmed that immune systems and resilient organizations are the most effective strategy for responding to non-routine risks (law probability and catastrophic consequences events).